Microbial Diversity in Cold Desert Ecosystem: A Review and Bibliometric Analysis - Chauhan, Mansi; Anita Pandey (Annals of Arid Zone, 2024)
Cold deserts play a unique and crucial role in the environment. Glaciers in these regions store significant amounts of freshwater, essential for ecosystems, while permafrost sequesters large quantities of carbon, preventing the release of greenhouse gases. These areas host diverse species, contributing to global biodiversity and a variety of extremophile life forms. The microbial communities in cold deserts—comprising bacteria, cyanobacteria, archaebacteria, fungi, and lichens—have adapted to harsh conditions. They maintain ecological balance by forming symbiotic interactions with plants, enhancing soil fertility, and boosting crop yields. Additionally, several microorganisms are involved in bioremediation processes. Microorganisms found in cold desert environments also serve as valuable biosignatures for detecting life, significantly advancing the field of astrobiology. This review explores the microbial diversity of cold deserts through bibliometric analysis using VOSviewer software. The software identified 47 countries engaged in cold desert research, with the United States leading in the number of publications. A total of 2009 keywords were analyzed, with "bacteria (microorganisms)" being the most common. This review encompasses studies on the microbial diversity of cold deserts and their applications, highlighting crucial directions for future research